2020
DOI: 10.3390/children7110235
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Quality of Life among Mothers in an Online Health Community for Children with Type 1 Diabetes

Abstract: Quality of life of parents of children with chronic disease is important for disease self-management. This study aimed to identify predictors of quality of life among mothers of children with type 1 diabetes. A cross-sectional study was conducted. A total of 208 mothers of children with type 1 diabetes were recruited from an online health community. Online health community collective empowerment and social support, diabetes self-efficacy, diabetes-related burden, and quality of life were measured. A multiple r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…T1D is among the diseases with the highest caregiver burden [ 24 ]. Numerous studies have shown that the burden of caring for mothers with a child with diabetes drastically reduces their quality of life [ 25 28 ]. Even the sleep of the parents of a child with diabetes is severely affected [ 29 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…T1D is among the diseases with the highest caregiver burden [ 24 ]. Numerous studies have shown that the burden of caring for mothers with a child with diabetes drastically reduces their quality of life [ 25 28 ]. Even the sleep of the parents of a child with diabetes is severely affected [ 29 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, by 2050, 600,000 children and adolescents under 20 will have type 1 diabetes [9]. Uhm and Kim [10] identified factors that influence a mother's quality of life while she has type 1 diabetes and developed novel diabetes management strategies. Dumas et al [11] discovered no effect on mothers' nutritional intake, food-related behaviors, or body weight at 6 months when they received one post each week.…”
Section: Introductionmentioning
confidence: 99%
“…2 Most qualitative studies on parents’ experiences of caring for children with T1D have been conducted with mothers, which relates to mothers shouldering the main caring responsibilities in diabetes care. 3 Similarly, in South Korea, mothers are mainly in charge of daily diabetes management, 4 and they are more actively involved in school health care (SHC) for their children’s chronic disease than fathers. 5 Mothers reported higher parental burden and emotional stress than fathers did.…”
mentioning
confidence: 99%